Phytochemical characterization and potential use in veterinary medicine of propolis of arid regions from northwest Argentina - Salas, Ana Lilia (2013)
In previous reports was demonstrated the antibacterial activity of propolis hydroalcoholic extracts from arid and semi-arid regions from northwest Argentina against human pathogens. The objective of this study was to compare two extraction methods of propolis from arid regions, and evaluate the antibacterial activity against bacteria isolated from canine otitis. Materials and methods: Propolis extract were prepared by successive extractions and maceration using ethanol 80°. Extracts were characterized by TLC and HPLC-DAD, and the total phenolics compounds, flavonoids and non flavonoids phenolic compounds content were determined by spectrophotometric methods. Minimal inhibitory concentration (MIC) values were determined by agar macrodilution method against 11 strains isolates from canine otitis (Staphylococcus and Proteus). Results: Four compounds (two chalcones, one flavone and one flavanone) were identified. Propolis tincture showed MIC values of 33 µg/ml and 267 µg/ml for the Gram- positive and Gram- negative bacteria, respectively. Conclusion: the propolis of arid regions from northwest Argentina may be used in veterinary medicine.